The History of Islamic Education During the Era of the Khulafaur Rasyidin: Pendidikan Islam, Masa Khulafaur Rasidin - Hasibuan, Rusdi Indra (The Future of Education Journal, 2025)
The purpose of this writing is to conduct a deeper study of the history of Islamic education during the era of the Khulafaur Rasyidin. Related to the history of education during the time of Prophet Muhammad SAW, education during his time became the foundation for the Islamic education system in the era of the Khulafaur Rasyidin. The Prophet emphasized education based on the Qur'an and Sunnah, with the mosque as the center of learning activities and exemplary behavior as the main method. During the Khulafaur Rasyidin period, this system was continued and developed as the Islamic territories expanded. The companions played the role of teachers in various regions, institutions such as kuttab and halaqah were established, and the codification of the Qur'an was carried out. Thus, the education during the Khulafaur Rasyidin period is a continuation and development of the education system that had been laid down by Prophet Muhammad SAW, which was initially carried out secretly or from house to house during the time when the Muslim community was a minority in Mecca. After Islam spread rapidly and gained many followers, education was conducted openly, starting particularly after Umar bin Khattab converted to Islam. Education continued to be carried out openly, leading to the history of Islamic education during the era of the Khulafaur Rasyidin. This research uses a critical historical approach through literature review. The research process follows four steps. First, the collection stage, which involves gathering, finding, and analyzing various historical sources. Second, the source verification stage, which tests the validity of the data by checking both internal and external sources. Third, the interpretation stage, which involves interpreting the information that has passed the verification process. Fourth, the presentation stage, which involves compiling the findings into a historical work. After the death of Prophet Muhammad SAW, the implementation of Islamic education continued with Islamic values by the Khulafaur Rasyidin. The Khulafaur Rasyidin led during four periods: the era of Abu Bakar ash-Shiddiq, the era of Umar bin Khattab, the era of Uthman bin Affan, and the era of Ali bin Abi Talib.